Validity and Reliability Test of COPSOQ III Questionnaire for Health Workers at RSUD X Year 2025 - Prameswari, Widya (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Job stress in healthcare workers can affect their mental and physical health. The causes of occupational stress in healthcare workers can vary, including high workload, high work pressure, long working hours and risk of exposure to disease. The COPSOQ III is an instrument that can be used to measure psychosocial factors in the workplace. This study aims to test the validity and reliability of the COPSOQ III (Copenhagen Psychosocial Questionnaire) questionnaire on health workers at X Hospital. The research design used was cross sectional. The research sampling was conducted using probability sampling method with simple random sampling technique on health workers at RSUD X. The validity test using Pearson correlation showed that all items were valid (r-count > 0.374), while the reliability test obtained a Cronbach's Alpha value of 0.903, indicating high consistency.